PENGABDIAN MASYARAKAT: SINERGI MAHASISWA DAN WARGA DESA RASAU JAYA TIGA DALAM PEMBERDAYAAN POTENSI LOKAL - Reswari, Rianti Ardana; Ine Chintya, Putri (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2025)
Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student dedication to society through the application of knowledge gained during university studies. The KKN program by Group 5 of Panca Bhakti University was carried out in Rasau Jaya Tiga Village, Rasau Jaya District, Kubu Raya Regency, for one month (August 1–31, 2025). The village is predominantly inhabited by farmers and faces several issues, such as the lack of awareness of the importance of higher education, healthy living practices, cleanliness of religious facilities, and support in the agricultural sector. The work programs implemented included higher education awareness campaigns, socialization on the role of parents in shaping youth character, processing kitchen waste into liquid organic fertilizer, morning exercise, community service, waste bin construction, installation of a non-Muslim cemetery signboard, and mapping local MSMEs through Google Maps. In addition, students participated in village activities, including serving as committee members for the 80th Independence Day celebration. All programs were successfully implemented and received positive responses from the community, with the hope of creating sustainable impacts for Rasau Jaya Tiga Village.